2015
DOI: 10.1161/atvbaha.115.305365
|View full text |Cite
|
Sign up to set email alerts
|

Circulating FABP4 Is a Prognostic Biomarker in Patients With Acute Coronary Syndrome but Not in Asymptomatic Individuals

Abstract: Objective— Blood-borne biomarkers reflecting atherosclerotic plaque burden have great potential to improve clinical management of atherosclerotic coronary artery disease and acute coronary syndrome (ACS). Approach and Results— Using data integration from gene expression profiling of coronary thrombi versus peripheral blood mononuclear cells and proteomic analysis of atherosclerotic plaque–derived secretomes versus healthy tissue secretome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…12,13 Another study found that circulating FABP4 predicted the risk of adverse cerebrovascular or cardiovascular events in patients with acute coronary syndrome but not in asymptomatic individuals. 27 The underlying mechanisms linking FABP4 with cardiometabolic conditions are illustrated in animal studies. In obese mice, the use of a small molecular inhibitor of FABP4 or targeted deletion of FABP4 could protect against the development of insulin resistance and lipid dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Another study found that circulating FABP4 predicted the risk of adverse cerebrovascular or cardiovascular events in patients with acute coronary syndrome but not in asymptomatic individuals. 27 The underlying mechanisms linking FABP4 with cardiometabolic conditions are illustrated in animal studies. In obese mice, the use of a small molecular inhibitor of FABP4 or targeted deletion of FABP4 could protect against the development of insulin resistance and lipid dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, FABP4 has been related to subclinical coronary atherosclerosis in type 2 diabetes mellitus subjects (Bagheri et al 2010), and circulating FABP4 levels are also associated with increased carotid intima-media thickness, ischaemic stroke, coronary atherosclerotic burden and the number of stenotic coronary arteries , Rhee et al 2009, Miyoshi et al 2010, Bao et al 2011, Doi et al 2011, Holm et al 2011, Tso et al 2011, Huang et al 2013. Recently, FABP4 has been proposed as a prognostic biomarker in patients with acute coronary syndrome (Reiser et al 2015). In addition, FABP4 is an important predictor of cardiovascular outcomes in patients with either coronary heart disease or acute ischaemic stroke (Holm et al 2011, von Eynatten et al 2012.…”
Section: Fabp4 As a Cardiometabolic Predictor For Cvdmentioning
confidence: 99%
“…Functions of the fatty acid-binding protein (FABP) gene family have been connected with the uptake, transportation and metabolism of intracellular free fatty acids (Migdał et al, 2018). Polymorphisms of the A-FABP gene are found to be prognostic biomarkers in patients with acute coronary syndrome (Reiser et al, 2015) and type 2 diabetes mellitus (Alqahtani et al, 2016). They are usually researched as candidate genes that affect the deposition of intramuscular fat in pigs (Zhang et al, 2013), cattle (Jurie et al, 2007), chickens (Zhou et al, 2018), ducks (Saez et al, 2009), goats (Wang, Geng, Ji, & Chang, 2012) and sheep (Wang et al, 2014).…”
mentioning
confidence: 99%